Discovery Learning Model: Concepts, Implementation, and Current Research Trends: Model Pembelajaran Discovery Learning: Konsep, Implementasi, dan Tren Penelitian Terkini - nihla utami; Lalu Arju (Science Education Doctoral Study Program, Postgraduate, Mataram University, 2025)
This study discusses the Discovery Learning learning model that emphasizes the active learning process where students independently discover concepts and principles through the stages of problem orientation, data exploration, information processing, verification, and reflection. This model is based on the principles of constructivism and student-centered learning, thereby increasing engagement and in-depth understanding of concepts. The advantages of Discovery Learning are the development of critical thinking skills, creativity, learning independence, and student learning motivation. This study uses a literature review method by analyzing relevant indexed scientific literature. The results of the study show that the implementation of Discovery Learning is effective in improving the quality of learning, but requires teacher readiness and careful planning. The latest trends also incorporate digital technology to enrich the student discovery process.